2020
DOI: 10.1093/heapol/czaa102
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives and practices of healthcare providers and caregivers on healthcare-associated infections in the neonatal intensive care units of two hospitals in Ghana

Abstract: Healthcare-associated infections (HAIs) remain a serious threat to patient safety worldwide, particularly in low- and middle-income countries. Reducing the burden of HAIs through the observation and enforcement of infection prevention and control (IPC) practices remains a priority. Despite growing emphasis on HAI prevention in low- and middle-income countries, limited evidence is available to improve IPC practices to reduce HAIs. This study examined the perspectives of healthcare providers (HPs) and mothers in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 68 publications
0
9
0
Order By: Relevance
“…As for the direct positive link between attitudes and IPC practice, this may lie in the fact that IPC practice was more likely to be driven by subjectively held information. 35 Similarly, Sunkwa-Mills et al 37 demonstrated that positive attitudes of some HCWs promoted standard IPC practice. Previous studies also indicated that believing one’s own behavior can change HCAIs outcomes is essential to achieving sustained behavior change.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As for the direct positive link between attitudes and IPC practice, this may lie in the fact that IPC practice was more likely to be driven by subjectively held information. 35 Similarly, Sunkwa-Mills et al 37 demonstrated that positive attitudes of some HCWs promoted standard IPC practice. Previous studies also indicated that believing one’s own behavior can change HCAIs outcomes is essential to achieving sustained behavior change.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, previous studies demonstrated that lack of time and excess workload were main barriers hindering adherence to IPC precautions, particularly in busy clinical work environment. 14 , 33 Sunkwa-Mills et al 37 also reported that HCWs sometimes regarded HCAIs concerns as secondary when faced with heavy clinical workload. Lien et al 34 also found that physicians complained that patient overload was a dominant barrier for their IPC compliance.…”
Section: Discussionmentioning
confidence: 99%
“…Hospital-acquired infections (HAIs) remain a concern of utmost importance in neonatal intensive care units (NICUs) [1]. HAIs contribute to a large number of neonatal morbidity and mortality [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…The Ghana Health Service (GHS) and other agencies of the Ministry of Health (MOH) are paying attention to issues of quality service delivery, having put in place some strategies to improve care [9]. Despite efforts by GHS and the MOH to improve the quality of care, there are health system challenges in the implementation of IPC interventions [10][11][12][13]. The COVID-19 pandemic was a further reminder of the risks that healthcare workers face from exposure to HAIs in hospital wards [14].…”
Section: Introductionmentioning
confidence: 99%